PEMANFAATAN VIRTUAL REALITY DALAM MATA PELAJARAN IPA DI SEKOLAH DASAR - Nurul Fitri Azizah; Marisa Marisa (Smart Education, 2024)
Abstract: This research aims to see the extent to which virtual reality is used in science subjects in elementary schools to increase student interaction in learning. The method in this research is a survey method, by observing and giving questionnaires to class VI students at SDN Buluh 02, Pacet, Bandung Regency in the Solar System subject. The research results show that student interaction in learning increases. Students also become more active in the learning process. The driving factor for student interaction and involvement is that virtual reality learning media provides experiences in the form of virtual displays that resemble real conditions so that students are interested in being involved in the learning process. Keywords: virtual reality, natural science, solar system Abstrak: Penelitian ini bertujuan untuk melihat sejauh mana pemanfaatan virtual reality pada Mata Pelajaran IPA di sekolah dasar untuk meningkatkan interaksi siswa dalam pembelajaran. Metode dalam penelitian ini adalah metode survey, dengan melakukan observasi dan memberikan kuesioner kepada peserta didik kelas VI di SDN Buluh 02, Pacet, Kabupaten Bandung dalam mata pelajaran Tata Surya. Hasil penelitian menunjukkan bahwa interaksi siswa dalam pembelajaran meningkat. Siswa juga menjadi lebih aktif dalam proses pembelajaran. Faktor pendorong interaksi dan keterlibatan siswa adalah karena media pembelajaran virtual reality memberikan pengalaman berupa tampilan virtual yang menyerupai kondisi nyata, sehingga siswa tertarik untuk terlibat dalam proses pembelajaran. Kata kunci: virtual reality, Ilmu Pengetahuan Alam, tata surya.